Promotion Mix from the Perspective of Islamic Marketing Management - Agustina, Abdul Gopur (Islamicate Institute, 2024)
This study examines the promotion mix from the perspective of Islamic marketing management. Using a normative qualitative methodology, it explores how advertising, sales promotion, and public relations can be adapted to comply with Sharia principles. Findings show that Islamic promotion emphasizes honesty, fairness, and social responsibility, prohibiting exaggeration and manipulation common in conventional practices. Case studies from Indonesian businesses demonstrate that Sharia-compliant promotion enhances consumer trust and strengthens long-term competitiveness. However, challenges persist in regulatory consistency, corporate commitment, and consumer literacy. The study contributes to theoretical discourse by operationalizing Islamic ethics within the promotion mix and provides practical recommendations for businesses and regulators. By adopting Sharia-compliant promotion, organizations can achieve both ethical integrity and sustainable competitive advantage.